Electromagnetic Waves from Mobile Phones may Affect Rat Brain During Development - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2021)
AIM: To investigate the effects of electromagnetic waves (EMWs) from mobile phones (MPs) on rat brains of rats by morphological and biochemical analysis. MATERIAL and METHODS: EMW was applied for two hours/day until birth in stand-by fetal and EMW fetal groups and postnatal 60th day in stand-by and EMW groups. The control group was not exposed to MP. On postnatal 60th day, brain malondialdehyde (MDA) and glutathione (GSH) levels were measured, and western blot analysis was performed to determine glial fibrillary acidic protein (GFAP) content. Hematoxylin and eosin staining and GFAP immunohistochemistry were applied. Trigeminal nerves were examined using the transmission electron microscope. RESULTS: In comparison to controls, rats exposed to MP in stand-by or talk modes had significantly increased neuronal damage in the cortex and hippocampus. Increased MDA levels in the EMW group and decreased GSH levels in the stand-by, EMW fetal and EMW groups were found compared with controls. Increased GFAP content in the EMW group and increased GFAP staining in the EMW fetal and EMW groups compared to controls were observed. EMW group had a significantly decreased number of myelinated axons than control animals. CONCLUSION: The results of this study suggests that 1800 MHz EMWs (SAR=1.79 W/kg) exposure in the prenatal and early postnatal life may lead to trigeminal nerve damage in addition to oxidative stress-induced neuronal degeneration and astroglial activation in the rat brain. Effects seem to be mode related, being more detrimental in groups exposed to MP during talk mode.
Keywords: Cell phone; Electromagnetic wave; Trigeminal nerve; Rat; Oxidative stress; BEHAVIORAL-PROBLEMS; POSTNATAL EXPOSURE; OXIDATIVE STRESS; RADIOFREQUENCY; FIELDS; INJURY; DAMAGE; GFAP; DYSFUNCTION; RADIATION